Indigenous Perspectives at the Cultural Interface: Exploring Student Achievement through School/Community-Based Interventions - Deer, Frank; Heringer, Rebeca (Canadian Journal of Education / Revue canadienne de l'éducation, 2023)
Many schools, school districts, and provincial education authorities in Canada are collaborating with Indigenous communities to indigenize content and provide progamming to improve Indigenous student success. With a focus on high school achievement in the area of Indigenous education at the cultural interface of Indigenous communities and Euro-Western educational systems, this article examines the efforts of a school division to impact student achievement and experience. Data from interviews conducted with teachers, educational assistants, and administrators are presented and discussed, evidencing participants’ perspectives on these initiatives. This study revealed that, despite numerous institutional and non-institutional challenges, the school division’s efforts in Indigenous education programming in many of its high schools have been thriving and have also been well supported compared to other public school divisions in Canada.